Perekrutan di negara ketiga: Kasus Pekerja Filipina Luar Negeri di Taiwan hingga Polandia - Anna Joceline Dizon Ituriaga (Jurnal HAM, 2024)
This study explores the complexities of third-country serial labor migration among Filipino factory workers, specifically those moving from Taiwan to Poland"”an activity deemed illegal by the Philippine government. Utilizing qualitative methods, the research conducts in-depth interviews with participants like Mae, Rick, and Justin, complemented by a key informant interview. The findings reveal a nuanced decision-making process, with participants expressing a desire for enhanced job conditions, contractual flexibility, and career advancement opportunities in Poland. Despite the Philippines' oversight and support for temporary migration, the practice of third-country hiring raises legal and ethical concerns. Without proper authorization from the Philippine government, recruiting workers through a third country is deemed illegal. To protect migrant workers, established procedures, including obtaining an Overseas Employment Certificate (OEC), are implemented to ensure lawful deployment. This study contributes to the ongoing discourse surrounding serial labor migration, providing valuable insights that can inform policy frameworks and practices aimed at enhancing the welfare and protection of migrant workers within the global labor market. Through analysis of the experiences and challenges faced by Filipino factory workers engaging in third-country migration, this research seeks to promote a deeper understanding of the complexities inherent in labor migration processes and advocate for measures to safeguard the rights and well-being of migrant workers worldwide.